(untitled) (World Economics and Finance Bulletin, 2024)
Islamic financial institutions were established with the aim of promoting and developing sharia principles. Sharia business in Islam must be run with good governance because it is seen as one of the manifestations of worship or good deeds based on piety, so adherence to spiritual and operational principles is required. This study aims to answer questions regarding the management of Infak Linked Business (ILB) funds and the implementation Good Governance of Sharia Business. This type of qualitative research uses a case study approach by focusing on only one side of the ILB funds GGBS which is then analyzed interactively. The results of the study show that the management of ILB funds that is carried out from upstream to downstream is the sharia supervisory division. The development of infaq funds is carried out in the business and investment sectors. The ILB fund management model is an application of ZISWAF fund management to the real or productive sector as in the 2019-2024 Islamic economic master plan. The implementation of GGBS ILB funds is aligned with a score of 31 out of 36 indicators, because the ILB fund management division is socially oriented while GGBS is an index for sharia business entities.